2018
DOI: 10.1186/s13071-018-3161-5
|View full text |Cite
|
Sign up to set email alerts
|

Dog survey in Russian veterinary hospitals: tick identification and molecular detection of tick-borne pathogens

Abstract: BackgroundSpecies of Canidae in Russia can be infested with up to 24 different tick species; however, the frequency of different tick species infesting domestic dogs across Russia is not known. In addition, tick-borne disease risks for domestic dogs in Russia are not well quantified. The goal of this study was to conduct a nationwide survey of ticks collected from infested dogs admitted to veterinary clinics in Russian cities and to identify pathogens found in these ticks.MethodsTicks feeding on dogs admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 43 publications
(35 reference statements)
3
24
0
3
Order By: Relevance
“…Furthermore, A. ovis (79.0%), A. bovis (24.7%), and A. phagocytophilum (28.4%) in Yecheng sheep in current study, while A. ovis (1.5%), A. marginale (5.7%), and A. centrale (2.7%) were identified in ticks from Pakistan, the country that Yecheng borders (25). Other border countries of XUAR also have reports about Anaplasma infection (A. bovis, A. centrale, A. phagocytophilum, and A. marginale) in ruminants or ticks including Russia (26), Philippines (27), and south India (28). Notably, A. capra, a newly discovered emerging zoonotic species of Anaplasma, was not identified in the current study, although it has been reported in both XUAR (only four positive samples) and Gansu of China (29,30).…”
Section: Resultsmentioning
confidence: 42%
“…Furthermore, A. ovis (79.0%), A. bovis (24.7%), and A. phagocytophilum (28.4%) in Yecheng sheep in current study, while A. ovis (1.5%), A. marginale (5.7%), and A. centrale (2.7%) were identified in ticks from Pakistan, the country that Yecheng borders (25). Other border countries of XUAR also have reports about Anaplasma infection (A. bovis, A. centrale, A. phagocytophilum, and A. marginale) in ruminants or ticks including Russia (26), Philippines (27), and south India (28). Notably, A. capra, a newly discovered emerging zoonotic species of Anaplasma, was not identified in the current study, although it has been reported in both XUAR (only four positive samples) and Gansu of China (29,30).…”
Section: Resultsmentioning
confidence: 42%
“…In Russia, the prevalence rates of Babesia spp. for questing adults of I. ricinus and D. reticulatus were, respectively, 3.9% and 20.3% [67].…”
Section: Resultsmentioning
confidence: 94%
“…A diversity of tick-borne pathogens, including Anaplasma, Babesia, Borrelia, Ehrlichia and Theileriai spp. has recently been molecularly detected in Russia (Livanova et al 2018 ). This, together with the present findings, draw the attention to not-yet known risks associated with tick-borne rickettsiae in several regions of Asia.…”
Section: Discussionmentioning
confidence: 99%